NON-FARM EMPLOYMENT REPORT TRADING WITH BINARY OPTIONS & TEMPORAL FUNCTIONALITIES - Basdekidou, Vasiliki A. (Annales Universitatis Apulensis Series Oeconomica, 2017)
The main target of this paper is to discuss a short-term strategy for trading the monthly USA Nonfarm Employment Reports (NFP; Non-Farm Payrolls), by incorporating binary options and temporal warning dynamics & triggering trading functionalities (TTF). The proposed trading strategy is not a fully documented trading system, because it is derived, as well as it has been back-tested on USA Markets sample data (2000-2016) with an initial formal definition and documentation. The nonfarm employment reports are well known to create market volatility fostering short-term trading. Hence, a strategy based on binary options and these TTF functionalities offer great profit opportunities. The current paper contributes to corporate finance literature by examining, analyzing and defining these TTF functionalities. For this purpose, four categories of shareholders are regarded: The long-term investors, the short-term swing traders, the short-term momentary speculators, and the intraday speculators. Paper concludes that, in daily and intraday NFP trading, the short-term swing traders -if they incorporate binary options and apply the proposed TTF in their trading plans and strategies- are benefit at the expense of momentary and intraday speculators, while the long-term investors are not actually affected by the NFP release reports trading.